Detours on the phloem sugar highway: stem carbon storage and remobilization. (June 2018) - Furze, Morgan E; Trumbore, Susan; Hartmann, Henrik
Highlights: Tree stems are more than a conduit for phloem C transport; they are a significant C sink. Isotopes demonstrate most phloem-transported C exchanges with NSC stored in stems. Exchange timescales are days, weeks or years, reflecting processes from mixing to remobilization. Abstract : For trees to survive, they must allocate resources between sources and sinks to maintain proper function. The vertical transport pathway in tree stems is essential for carbohydrates and other solutes to move between the canopy and the root system. To date, research and models emphasize the role of tree stems as 'express' sugar highways. However, recent investigations using isotopic markers suggest that there is considerable storage and exchange of phloem-transported sugars with older carbon (C) reserves within the stem. Thus, we suggest that stems play an important role not only in long-distance transport, but also in the regulation of the tree's overall C balance. A quantitative partitioning of stem C inputs among storage and sinks, including tissue growth, respiration, and export to roots, is still lacking. Combining methods to better quantify the dynamics and controls of C storage and remobilization in the stem will help to resolve central questions of allocation and C balance in trees.